De artículos de primera necesidad a necesidades básicas insatisfechas. Una mirada al proyecto de bienestar en el siglo xx uruguayo a través del debate sobre el costo de vida - Aldo Marchesi (Historia Crítica, 2023)
Objective/Context: This article studies how the Uruguayan State conceptualized the idea of “necessity” in relation to the welfare project throughout the twentieth century. Throughout the first half of the century, the Uruguayan State developed a sustained policy of price control based on the concept of basic necessities. During the second half, the system began to crumble under the growing influence of liberal economic approaches and authoritarian processes. In the democratic revival context of the 1980s, these ideas began to be replaced by the concept of unsatisfied basic needs based on the influence of international organizations. Methodology: Through a methodological approach that focuses on the debates in Parliament and the public sphere, the text studies different meanings associated with the idea of necessity in relation to welfare. Originality: The documentary review offers an unprecedented journey through the transformations of the notion of necessity, showing that, while in the 1920s, the products were related to food, in the 1940s, they expanded to include multiple goods associated with the standard of living of the middle class. Simultaneously, the State developed commercial intermediation activities and promoted regulatory mechanisms that sought to control prices and ensure the supply of these goods. From the 1970s onwards, the concept of unsatisfied basic needs contributed to restricting the social role of the State by transforming the idea of welfare linked to universalist policies for the popular sectors to the development of targeted policies aimed at sectors below the poverty line. Conclusions: These policy debates transcended political-ideological alignments and were sustained by relatively shared principles of moral economy that varied between the first and second half of the 20th century.